The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/07448481.2019.1709474
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in a sample of UK college students: a study of prevalence, comorbidity, and quality of life

Abstract: This study sought to estimate the prevalence of depression and anxiety in UK college students and examine associations between mental health symptoms and quality of life (QoL). Associations between psychiatric comorbidity and degree of QoL impairment were also investigated.Participants: Participants (N = 286) were recruited from a UK university (76.1% ≤20 yearsold; 86.8% female; 71.1% White). Methods: Self-report measures of depression, anxiety, and QoL were completed online.Group differences and within-group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 34 publications
4
55
2
2
Order By: Relevance
“…The present student sample reported moderate (26%) rates of current mental health problems in line with recent student population estimates [ 4 , 10 , 72 ]. Commonly, mindfulness practitioners advise against participation in MBPs if a potential participant is experiencing severe psychological distress, current depression, mania, or recent bereavement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present student sample reported moderate (26%) rates of current mental health problems in line with recent student population estimates [ 4 , 10 , 72 ]. Commonly, mindfulness practitioners advise against participation in MBPs if a potential participant is experiencing severe psychological distress, current depression, mania, or recent bereavement.…”
Section: Discussionsupporting
confidence: 91%
“…The negative impact of having a mental health problem during university is broad, impacting the quality of life. Specifically, the presence of depressive symptoms in university students has been associated with role limitations due to physical health problems; while anxiety symptoms have been related to bodily pain; and both depressive and anxiety symptoms have been associated with reductions in general health, energy/fatigue, social functioning, as well as psychological distress, and lower psychological wellbeing [ 10 ]. It has also been observed that mental health problems during university affect academic performance [ 11 ] and the likelihood of dropping out [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is now su cient evidence to state that the female gender is a reliable risk factor for depressive and anxiety symptoms [5,17,32,35]. The gender difference was veri ed in our study.…”
Section: Discussionsupporting
confidence: 68%
“…Much of the evidence emerges with the overlaps between depressive and anxious symptomatology based on the community-based estimates of categorical groups of afflicted individuals as defined in nosological classifications (Jenkins et al 2020;Price et al 2019;Routledge et al 2017;Taporoski et al 2015). One of the most prevailing notions in regard to the affect regulation is the two-dimensional approach in which the Negative Affect (NA) constitutes one pole generally related to subjective distress, and the Positive Affect (PA) constitutes the other referring to happiness, with stronger linkages to sad mood relative to fear (Watson and Tellegen 1985;Watson et al 1999).…”
Section: Tripartite Model Of Depression and Anxietymentioning
confidence: 99%